Training on Contemporary Learning Models to Improve the Ability of Teachers of SMAN 2 Painan to Perform Classroom Action Research - Hendra Syarifuddin (Pelita Eksakta, 2020)
To help the teachers of SMAN 2 Painan improve their ability to implement contemporary learning models in CAR activities, this community service activity is carried out in the form of training. The materials that will be given during the training are focused on the following matters; 1) various contemporary learning models and how to implement them, 2) general description of CAR (definition, goals, benefits), preparation of proposals, and reporting, 3) various approaches / models / methods / strategies in learning that might be adopted. This activity aims to help the teachers of SMAN 2 Painan to improve their knowledge and skills in applying constructivism-based learning models in classroom action research. Specifically, after this activity the teachers of the Painan 2 High School have the ability to; 1) implementing learning models based on constructivism, 2) reflecting on their learning practices, 3) selecting and applying the learning methods / models / strategies they choose as remedial actions, 4) determining and developing suitable PTK instruments, 5 ) analyzing quantitative and qualitative data, 6) preparing CAR proposals, 7) preparing final reports, and 8) writing scientific articles based on CAR. This activity has a direct benefit for the teachers of SMAN 2 Painan in their efforts to improve their learning practices, and this is determined to have a positive effect on student optimization in learning.